Efficacy and safety of ultrasound-guided internal jugular vein catheterization in low birth weight newborn - Montes Tapia, Fernando Félix; Rodríguez Taméz, Antonio; Cura Esquivel, Idalia Aracely; Rodríguez Balderrama, Isaías; De la O Cavazos, Manuel Enrique (W.B. Saunders Co., 2016)
Central venous catheterization is not the first choice of vascular access in neonates. Success depends on the size of the vessel and the skill of the health professional performing the procedure. The internal jugular vein provides a predictable path for central venous cannulation, although it is more difficult to cannulate infants than adults and even more difficult in smaller newborns. METHODS: We conducted a prospective study in 100 newborns, in which a 4 Fr ultrasound-guided central venous catheter was placed in the right internal jugular vein (RIJV). The study population was low birth weight (LBW) newborns <2500g, very low birth weight (VLBW) newborns <1500g and extremely low birth weight (ELBW) newborns <1000g. RESULTS: Background:There were 53% female patients, mean gestational age was 31weeks, mean weight 1352g and the CVC was placed at a mean of 12days of extrauterine life. Birth weight distribution was 39% LBW; 33% VLBW and 28% ELBW. A mean of two (1-8) attempts were necessary with a procedure duration of 16.8 (10-40) minutes. Success of RIJV catheterization was 94%. One attempt was necessary in 50% and up to 5 attempts in 95.7%. Success by weight was VLBW, 97.2%; ELBW, 92.9%; LBW, 91.7%. A venous hematoma occurred in 5% of cases. CONCLUSIONS: Ultrasound-guided RIJV cannulation with real-time visualization to gain access to the central venous circulation in low birth weight newborns is effective and safe.